Blood lead and cadmium levels are negatively associated with bone mineral density in young female adults - Jianfeng Lu; Ji Lan; Xiao'e Li; Zhongxin Zhu (BMC, 2021)
Abstract Background The organ toxicities of lead and cadmium have been extensively studied; however, studies of their toxic effects on bone remain limited, especially in young adults. The objective of this study was to examine the associations of blood lead levels (BLL) and blood cadmium levels (BCL) with bone mineral density (BMD) among young adults. Methods We performed a cross-sectional study using the National Health and Nutrition Examination Survey 2011-2018 database. Because of the skewed distribution, BLL and BCL were Ln-transformed for analysis. Weighted multivariate regressions were performed to evaluate the associations between LnBLL and LnBCL and lumbar BMD. Subgroup analyses were further performed. Results A total of 3234 participants aged 20-35 years were included in this study. No significant association between LnBLL and lumbar BMD was found (β = − 5.6, 95%CI: − 13.5-2.3). However, in the subgroup analysis stratified by sex, this association became negative in women (β = − 18.2, 95%CI: − 29.9- − 6.4). Moreover, this negative association was more prominent in female blacks (β = − 35.5, 95%CI: − 63.4- − 7.6). On the other hand, a negative association between LnBCL and lumbar BMD was found (β = − 7.4, 95%CI: − 14.0- − 0.8). In the subgroup analysis stratified by sex, this negative association only existed in women (β = − 18.7, 95%CI: − 28.0- − 9.5). Moreover, this negative association was more prominent in female whites (β = − 31.1, 95%CI: − 46.2- − 16.1). Conclusions Our finding showed that both BLL and BCL were independently and negatively associated with lumbar BMD among young females, but not among young males.